Surface morphology of amorphous SiO2 substrates bombarded with 1.0 MeV Si+ ions. (14th June 2018) - Garcia, M A; Rickards, J; Gago, R; Trejo-Luna, R; Cañetas-Ortega, J; de la Vega, L R; Rodríguez-Fernández, L
Abstract: Surface pattern formation on amorphous SiO2 substrates by implantation of 1.0 MeV Si + ions at a current of 1.3 µ A at 70° angle is reported. Surface micrometer sized ripples perpendicular to the ion beam direction are formed, observed by scanning electron microscopy and atomic force microscopy. The morphological features are more or less similar for different fluences. The formation of surface ripples at this energy is discussed in terms of ion stopping mechanisms and patterns obtained within the low- and medium-energy ranges.